Rezension zu Dagmar Abfalter und Rosa Reitsamer (Hg.) (2022) »Music as Labour – Inequalities and Activism in the Past and Present.« - Troike, Manuel (SAMPLES)

Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies)
Transformations of various kinds have always shaped societies and especially its cultures and research – triggered, for example, by wars, revolutions, shifts in social orders, pandemics, etc. They have led to uncertainty and social upheaval, but also to innovation and change. As pop music cultures, in their entire breadth, can be described as seismographs of social, political, economic, ecological, media, artistic, and technological transformations, in and through them, fields of tensions, disruptions, and lines of conflict become not only visible, audible, and perceptible, but also communicable and thus, negotiable. Volume No. 2 of ~Vibes – The IASPM D-A-CH Series, which is based on the 4th Biennial IASPM D-A-CH conference at Paderborn University/online, takes a closer look at the transformative moments of pop music cultures by theorizing, empiricizing, historicizing, and, finally, politicizing them.

Contradict – Ideas for a New World. A Talk between Thomas Burkhalter and Manuel Troike about the documentary film Contradict. - Burkhalter, Thomas; Troike, Manuel (Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies))
Manuel Troike talks to the Swiss ethnomusicologist Dr. Thomas Burkhalter about his music documentary Contradict – Ideas for a New World. Together with Peter Guyer, Burkhalter gives six musicians from Ghana a chance to speak, to look at the changing values of our time from the African continent, and to show how trends, ideas and visions are increasingly decentralised in a globalised world.

Das Party-Prekariat? - Troike, Manuel (PopEventKulturen an den Schnittstellen von Management und Politik)

Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies) – Introduction - Flath, Beate; Jacke, Christoph; Troike, Manuel (Transformational POP: Transitions, Breaks, and Crises in Popular Music (Studies))